Sustained drug retention after paclitaxel-coated balloon angioplasty for superficial femoral artery disease: Follow-up intravascular imaging. (February 2020) - Kobayashi, Norihiro; Hirano, Keisuke; Yamawaki, Masahiro; Araki, Motoharu; Sakai, Tsuyoshi; Sakamoto, Yasunari; Mori, Shinsuke; Tsutsumi, Masakazu; Nauchi, Masahiro; Sahara, Naohiko; Honda, Yohsuke; Makino, Kenji; et al.
A 63 year-old woman with claudication underwent endovascular therapy for diffuse stenosis of the right superficial femoral artery in our hospital. We performed paclitaxel-coated balloon angioplasty using the IN.PACT™ Admiral™ and achieved acceptable results. After 42 days, we performed follow-up optical frequency domain imaging for the right superficial femoral artery lesion treated with paclitaxel-coated balloon and observed several high-intensity regions with attenuation on the lumen surface. Sustained drug availability is a notable characteristic of paclitaxel-coated balloon. To the best of our knowledge, this is the first report on the visualization of sustained drug retention on the lumen surface using follow-up optical frequency domain imaging after paclitaxel-coated balloon angioplasty in a human patient with superficial femoral artery disease.